2018
DOI: 10.1007/s10048-018-0538-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and neuroimaging features of autosomal recessive spastic paraplegia 35 (SPG35): case reports, new mutations, and brief literature review

Abstract: Spastic paraplegia 35 (SPG35) is a recessive condition characterized by childhood onset, progressive course, complicated by dystonia, dysarthria, cognitive impairment, and epilepsy. Mutations in the FA2H gene have been described in several families, leading to the proposal of a single entity, named fatty acid hydrolase-associated neurodegeneration (FAHN). Several reports have described a polymorphic radiological picture with white matter lesions of various degrees and a distinct form of neurodegeneration with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 27 publications
2
19
2
Order By: Relevance
“…Mutations affecting the cytochrome b5-like heme binding domain and the fatty acid hydroxylase domain result in a reduction of the enzyme’s activity, as well as the possible disruption of the interaction of these domains with iron-containing ligands [ 145 ]. The reduction of the enzymatic activity or its complete depletion, caused by the different mutations located throughout the protein, could explain the variability in the severity of the phenotypes.…”
Section: Nbia Types Related To Lipid Metabolism and Membrane Remodmentioning
confidence: 99%
“…Mutations affecting the cytochrome b5-like heme binding domain and the fatty acid hydroxylase domain result in a reduction of the enzyme’s activity, as well as the possible disruption of the interaction of these domains with iron-containing ligands [ 145 ]. The reduction of the enzymatic activity or its complete depletion, caused by the different mutations located throughout the protein, could explain the variability in the severity of the phenotypes.…”
Section: Nbia Types Related To Lipid Metabolism and Membrane Remodmentioning
confidence: 99%
“…NBIAs are an expanding group of progressive diseases characterized by abnormal accumulation of iron in the brain, particularly the basal ganglia, caused by different mutations with different modes of inheritance (see Table 2; Akcakaya et al 2019;Mari et al 2018;Rattay et al 2019;Haack et al 2012;Marchi et al 2019) leading to neurodegeneration. Most patients present with movement disorders, particularly dystonia and parkinsonism.…”
Section: Neurodegeneration With Brain Iron Accumulation (Nbia)mentioning
confidence: 99%
“…A recent in silico protein modelling report demonstrated that the FAHN causative missense mutations alter the heme-binding site or disrupt the hydroxylase domain impairing the enzyme catalytic activity. However, the mechanism by which reduced FA2H activity generates the iron deposition was not investigated [79].…”
Section: Introductionmentioning
confidence: 99%